MAPPING SKINIMALISM NARRATIVES ON INSTAGRAM HASHTAG POSTS - Suryaneta, Suryaneta; Noviantoro, Tri; Nugraha, Andhyka Tyaz (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
Skinimalism has gained visibility as a beauty trend promoting fewer products, fewer routine steps, and deliberate essentials. This study maps how skinimalism is narrated in Instagram hashtag posts using qualitative netnographic observation and descriptive content analysis. Forty caption entries were purposively sampled from the #skinimalism feed; after removing near-duplicates, 36 unique captions were analyzed. Captions were predominantly in English (63.9%), followed by Indonesian (25.0%) and other languages (11.1%), with #skinimalism appearing explicitly in 80.6% of captions. Dominant narrative categories comprised trend definition or education (30.6%), product promotion (27.8%), and routine guidance (22.2%). Nonexclusive thematic coding revealed routine simplification as the most prevalent element (66.7%), followed by natural look aesthetics (33.3%), while multifunctionality or hybrid product framing was relatively limited (11.1%). Actor cues were identifiable in many posts, including brands or commercial accounts (22.2%), creators or educators (19.4%), clinics or experts (11.1%), and individual users (8.3%), although 38.9% could not be clearly classified. Engagement assessed from visible comment excerpts (n = 40) indicated limited discourse, with half of the posts showing no comments and the remainder dominated by emotive or transactional responses. This limited engagement does not necessarily signal weak consumer interest but reflects Instagram’s role in stabilizing trend narratives through curated, authored content. Overall, the hashtag feed functions as a structured narrative field that reinforces skinimalism through procedural templates and marketing-aligned messaging rather than extended peer deliberation.